Evaluating the Efficiency and Productivity Effects of Cross-Border Acquisitions Using Data Envelopment Analysis (DEA) - Syarifa Hanoum; Silviana Khalilatus Sa'adah; Irene Kanina Ratih; Jihan Rofifah; Uliyatun Nikmah; Mahmood Shubbak (International Journal of Business and Management Technology in Society, 2024)
Purpose – This research examines the impact of cross-border acquisitions on the efficiency and productivity of acquired companies, with a specific focus on MSA, an automotive firm. Methodology – We employ Data Envelopment Analysis (DEA) to assess total factor productivity and compare MSA’s performance before and after its acquisition by Michelin. Findings – MSA’s efficiency fluctuated over time, peaking in Q1 2021 with a score of 1 but declining in Q1 2022, indicating room for improvement. The Mann-Whitney test results show no significant change in MSA’s efficiency following the acquisition, suggesting the merger did not notably enhance performance. Practical implications – Managers should concentrate on optimizing material, labor, and capital management, while maintaining continuous operational monitoring. A proactive approach to the implications of strategic decisions, such as cross-border acquisitions, is essential for sustained high performance and long-term success.